A review of glioblastoma tumors with primitive neuronal component and a case report of a patient with this uncommon tumor at a rare location. Issue 12 (12th August 2020) - Shayganfar, Azin; Ebrahimian, Shadi; Mahzouni, Parvin; Shirani, Fattane; Aalinezhad, Marzieh
Abstract: Glioblastoma with primitive neuronal component should be considered as a differential diagnosis of infratentorial tumors. Abstract : Glioblastoma with primitive neuronal component should be considered as a differential diagnosis of infratentorial tumors.